Efficacy of Community Treatments for Schizophrenia and Other Psychotic Disorders: A Literature Review - Armijo, Julio; Mendez, Emmanuel; Morales, Ricardo; Schilling, Sara; Castro, Ariel; Alvarado, Rubén; Rojas, Graciela (Frontiers in Psychiatry, 2013)
Background: In Chile, the clinical guidelines “For the Treatment of People from First Episode of Schizophrenia” aim to support individuals with schizophrenia to live independently, establishment occupational goals, and gain an adequate quality of life and social interaction. This requires the implementation of a treatment model that integrates psychosocial and pharmacological dimensions. Community intervention strategies ensure the achievement of these goals. Objectives: This study compiles and synthesizes available scientific evidence from the last 14 years on the effectiveness of community intervention strategies for schizophrenia and related psychotic disorders. Methodology: An electronic search was carried out using PUBMED, LILACS and Science-Direct as databases. Criteria of inclusion: i: randomized clinical trials, ii. Community-based interventions, iii. diagnosis of schizophrenia or related psychotic disorder (section F2 of ICD-10). Exclusion Criteria: i. treatments exclusively pharmacological, ii. Interventions carried out in inpatient settings, ii. bipolar affective disorder or substance-induced psychosis (greater than 50% of sample). Results: 66 articles were reviewed. Community strategies for integrated treatment from the first outbreak of schizophrenia significantly reduced negative and psychotic symptoms, days of hospitalization, and comorbidity with substance abuse and improved global functioning and adherence to treatment. In other stages, there were improved outcomes in negative and positive symptoms and general psychopathology. Psychoeducation for patients and families reduced the levels of self-stigma and domestic abuse, as well as improved knowledge of the disease and treatment adherence. Training focused on cognitive, social, and labor skills has been shown to improve yields in social functioning and employment status. Conclusions: Community-based intervention strategies are widely supported in the treatment of patients with schizophrenia.